MicroRNA‐145‐5p regulates fibrotic features of recessive dystrophic epidermolysis bullosa skin fibroblasts - Condorelli, A.G.; Logli, E.; Cianfarani, F.; Teson, M.; Diociaiuti, A.; El Hachem, M.; Zambruno, G.; Castiglia, D.; Odorisio, T. (British journal of dermatology (1951), 2019)
Summary Background Recessive dystrophic epidermolysis bullosa (RDEB) is a skin fragility disorder caused by mutations in the COL7A1 gene encoding type VII collagen, a cutaneous basement membrane component essential for epidermal–dermal adhesion. Hallmarks of the disease are unremitting blistering and chronic wounds with severe inflammation and fibrosis. MicroRNAs (miRNAs) are post‐transcriptional regulators of gene expression also implicated in fibrotic processes. However, the role of miRNAs in RDEB fibrosis is almost unexplored. Objectives Our study aimed to identify miRNAs deregulated in primary RDEB skin fibroblasts (RDEBFs) and to characterize their function in RDEB fibrosis. Methods Real‐time quantitative polymerase chain reaction (qRT‐PCR) was used to screen RDEBFs for expression levels of a group of miRNAs deregulated in hypertrophic scars and keloids, pathological conditions with abnormal wound healing and fibrosis. Contractility, proliferation and migration rate were evaluated by different in vitro assays in RDEBFs transfected with a miR‐145‐5p inhibitor. Expression levels of fibrotic markers and miR‐145‐5p targets were measured using qRT‐PCR and western blot. Results The miR‐143/145 cluster was upregulated in RDEBFs compared with fibroblasts from healthy subjects. RDEBFs transfected with a miR‐145‐5p inhibitor showed attenuated fibrotic traits of contraction, proliferation and migration, accompanied by reduced expression of the contractile proteins α‐smooth muscle actin and transgelin. These effects were associated with upregulation of Krüppel‐like factor 4 transcriptional repressor and downregulation of Jagged1, a known inducer of fibrosis. Conclusions Our results highlight the profibrotic role of miR‐145‐5p and its regulatory networks in RDEB, shedding light on novel disease pathomechanisms and targets for future therapeutic approaches. What's already known about this topic? Recessive dystrophic epidermolysis bullosa (RDEB) is a highly disabling genetic skin disease caused by mutations in the collagen VII gene and characterized by unremitting blistering and defective wound healing, leading to inflammation and fibrosis. MicroRNAs (miRNAs) are post‐transcriptional regulators of gene expression in health and disease, and their deregulation has been implicated in fibrotic skin conditions. To date, only miR‐29 has been associated with injury‐driven fibrosis in RDEB. What does this study add? In patients with RDEB, miR‐145‐5p is overexpressed in RDEB skin fibroblasts (RDEBFs), where it plays a profibrotic role, as its inhibition reduces RDEBF fibrotic traits (contraction, proliferation and migration). miR‐145‐5p inhibition in RDEBFs determines the reduction of contractile markers α‐smooth muscle actin and transgelin through upregulation of Krüppel‐like factor 4, a transcriptional repressor of contractile proteins, and downregulation of Jagged1 (JAG1), an inducer of fibrosis. What is the translational message? Our findings expand the knowledge on miRNA‐driven pathomechanisms implicated in RDEB fibrosis. miR‐145‐5p and its targets (e.g. JAG1) could represent relevant molecules for the development of novel therapeutic strategies to counteract fibrosis progression in patients with RDEB. Linked Comment: Wally and Bauer. Br J Dermatol 2019; 181:890–891. Plain language summary available online Respond to this article